Heidi and the milk factory - Haq, Roohi (Karachi : Paramount books, 2014)
"Heidi and the Milk Factory" appears to be a story where a cow named Heidi has some connection to a milk factory. The illustration suggests a rural setting with green fields and cows. The book likely follows Heidi's experiences or adventures related to the production of milk at this factory.
Location: 3B
Keywords: Story book